"Look! It is not a bamoule!": 18‐ and 24‐month‐olds can use negative sentences to constrain their interpretation of novel word meanings. Issue 4 (12th February 2021) - de Carvalho, Alex; Crimon, Cécile; Barrault, Axel; Trueswell, John; Christophe, Anne
Abstract: Two word‐learning experiments were conducted to investigate the understanding of negative sentences in 18‐ and 24‐month‐old children. In Experiment 1, after learning that bamoule means "penguin" and pirdaling means "cartwheeling, " 18‐month‐olds ( n = 48) increased their looking times when listening to negative sentences rendered false by their visual context (" Look! It is not a bamoule! " while watching a video showing a penguin cartwheeling); however, they did not change their looking behavior when negative sentences were rendered true by their context (" Look! It is not pirdaling! " while watching a penguin spinning). In Experiment 2, 24‐month‐olds ( n = 48) were first exposed to a teaching phase in which they saw a new cartoon character on a television (e.g., a blue monster). Participants in the affirmative condition listened to sentences like " It's a bamoule! " and participants in the negative condition listened to sentences like " It's not a bamoule! ." At test, all participants were asked to find the bamoule while viewing two images: the familiar character from the teaching phase versus a novel character (e.g., a red monster). Results showed that participants in the affirmative condition looked more to the familiar character (i.e., they learned the familiar character was a bamoule) than participants in the negative condition. Together, these studies provide the first evidence for the understanding of negative sentences during the second year of life. The ability to understand negative sentences so early might support language acquisition, providing infants with a tool to constrain the space of possibilities for word meanings. Abstract : In this paper, two word‐learning experiments investigated the understanding of negative sentences in 18‐ and 24‐month‐old children. In Experiment 1, after having learnt that bamoule means "penguin" during a habituation phase, at test infants increased their looking times when they heard negative sentences that were rendered false by the context. In contrast, they did not change their looking behavior when listening to a negative sentence that was true in its context. In Experiment 2, children who witnessed a person label a monster using an affirmative sentence associated the novel word with the monster. However, children who witnessed the person label the monster using a negative sentence did not make the same association. Together, these studies provide the first evidence for the understanding of negative sentences during the second year of life.